PTERELLA GRISEA (MEIGEN, 1824), A SENIOR SYNONYM OF SETULIA ELEONORAE VENTURI, 1957 (DIPTERA, SARCOPHAGIDAE) - Daniel Whitmore (Fragmenta entomologica, 2008)
A lectotype is designated for Pterella eleonorae (Venturi, 1957), which is recognized as a junior synonym of Pterella grisea (Meigen, 1824), syn. nov. The Italian distribution of P. grisea is updated.